The Influence of Phototherapy on Recovery From Exercise-Induced Muscle Damage - Anthony D'Amico; Kevin Silva; Alejandro Rubero; Steven Dion; Jason Gillis; Joseph Gallo (International Journal of Sports Physical Therapy)
# Background